Supporting virtual teamwork in Collaborative Product Development. (1st January 2011) - Mengoni, Maura; Germani, Michele; Peruzzini, Margherita; Mandolini, Marco
The increasing product complexity and the continuous need of improving product quality and services force companies to join into distributed and extended networks. Collaborative product development triggers research toward the development of new methods and tools to manage virtual teamwork to reduce time to market. In this context, the paper proposes a novel approach and a supporting co-design platform to manage interrelations across organisations. Experimentations into four product design chains show improvements in communication, information sharing, knowledge distribution, time saving and easiness of team management. They demonstrate that collaborative product development can be usefully enhanced only if tools and procedures are designed for the specific needs of the virtual network.